Treatment with Molgramostim (Recombinant Human Granulocyte-Macrophage Colony Stimulating Factor, Rhugm-Csf, Mielogen) and Lenograstim (Granulocyte-Colony Stimulating Factor) Improves Experimental Colitis in Rats. (9th October 2019) - Papalois, Apostolos E.; Barbatis, Calypso; Chrysikos, Dimosthenis; Korontzi, Maria; Sideris, Michail; Pittaras, Theodoros; Triantafyllidi, Eleni; Nomikos, Alexandros; Triantafillidis, John K.
Abstract : Background/Aim. Treatment with growth factors could be beneficial in both inflammatory bowel disease and experimental colitis. The aim of this study was to investigate the effect of Colony Stimulating Factor (CSF), and Recombinant Human (rHu) Granulocyte Stimulating Factor (GSF) in experimental colitis in rats. Methods . Experimental colitis was induced in 62 male Wistar rats, divided into 9 groups, using 2, 4, 6-trinitrobenzensulfonic acid (TNBS). Group 1: Ten rats with colitis without treatment (control group). Euthanasia after 15 days. Group 2: Ten animals with colitis without treatment (control group). Euthanasia after 30 days. Group 3: Six animals with colitis. Immediate treatment with CSF. Euthanasia after 19 days. Group 4: Six animals with colitis. Treatment started 7 days after the induction of colitis. Animals were kept for 19 days. Group 5: Six animals with colitis. Treatment started 2 weeks after the induction of colitis. Group 6: Six animals with colitis, the same as in group 3. Treatment with GSF. Group 7: Six animals with colitis, the same as in group 4. Treatment with GSF. Group 8. Six animals with colitis, the same as in group 5. Treatment with GSF. Group 9: Six animals with colitis. Immediate treatment with prednisolone. Euthanasia after 15 days. Results . CSF and GSF administration significantly improved the histological score (P < 0.05 ) and reduced malondialdehyde contents (P < 0.05 ), compared to control groups in all animals. CSF was superior to GSF and to prednisolone. Conclusion . Administration of both CSF and GSF could significantly improve the histological score and oxidative stress in experimental colitis in rats.